2023
DOI: 10.3926/jotse.1902
|View full text |Cite
|
Sign up to set email alerts
|

Concept difficulty in secondary school chemistry: An intra-play of gender, school location and school type

Abstract: This study focused on addressing underperformance in chemistry in Anglophone West African countries. The main purpose of the study was to determine if factors such as gender, school location and ownership impact students’ perception of the difficulty of chemistry concepts and to suggest how these difficult concepts can be made easy to learn from the perspectives of the students. A mixed-methods approach was adopted. Participants were 1,292 chemistry students from nine public and 12 private secondary schools in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Concept difficulty refers to the degree to which a student can grasp an idea or issue (Oladejo et al, 2023). A considerable body of research has demonstrated that chemistry is a discipline that places significant cognitive demands on learners (Zoller & Tsaparlis, 1997).…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Concept difficulty refers to the degree to which a student can grasp an idea or issue (Oladejo et al, 2023). A considerable body of research has demonstrated that chemistry is a discipline that places significant cognitive demands on learners (Zoller & Tsaparlis, 1997).…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…The metacognitive thinking processes are verbalized by the teacher who is the expert learner in terms of metacognitive learning [4]. A question on the topic concentration is presented to the learners to solve: What is the concentration in mol dm −3 of a solution made from 7.31 g sodium chloride in 250 cm 3 of distilled water? The teacher models metacognitive thinking by thinking out loudly (verbalization) in the three phases of metacognitive learning (planning phase, monitoring phase and evaluation phase).…”
Section: Metacognitive Modeling By the Teachermentioning
confidence: 99%
“…Definition of concentration. Convert a given mass into mol and a given volume into dm 3 . Calculate concentration.…”
Section: Planning Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Variables that can be controlled experimentally are concentration, pressure, volume, and temperature. Students feel that chemistry is a complex subject, and students do not have a strong foundation before studying chemical equilibrium material, especially in the submatter of factors that affect chemical equilibrium (Belayneh & Belachew, 2023;Bernal-Ballen & Ladino-Ospina, 2019;Oladejo et al, 2023;Omilani & Elebute, 2020;Rahmawati et al, 2022). Chemical equilibrium matter is one of the abstract, defined, mathematical, and graphic complex matter.…”
Section: Introductionmentioning
confidence: 99%